Improving Dental Health Maintenance Knowledge and Attitudes of Elementary School Children through Android-Based Crossword Puzzle - Bedjo Santoso; Supriyana Supriyana; Bambang Sutomo (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2024)
Oral health is an integral part of overall body health. Clinical factors that cause dental caries in elementaryschool children are influenced by host, substart and time. Oral hygiene needs to be maintained from anearly age, especially in children in primary school. If this hygiene is neglected, it can have a negative impacton the child's debris index score. The School Dental Health Program (UKGS) aims to improve the dentalhealth of students in schools through various activities that are promotive, preventive, and curative forstudents who need treatment. One of the effective dental health education methods to be given to elementaryschool children is through crossword puzzles. The method of implementing this community service iscarried out by demonstration, training and assistance in brushing teeth in elementary school children. Basedon the results of community service carried out in primary school children, it can be concluded that there isan increase in children's knowledge and attitudes towards maintaining dental health.Keyword : dental health, children, brushing teeth